Role of Ionic Liquid-Based Multipurpose Gas Hydrate and Corrosion Inhibitors in Gas Transmission Pipeline - Qasim, A. (Springer Science and Business Media B.V., 2020)
Gas hydrate blockage and corrosion are two major flow assurance problems in oil and natural gas processing and transmission which cause severe safety and economic losses. The oil and gas industry has been injecting different types of corrosion as well as gas hydrate inhibitors to overcome these flow assurance problems in subsea flowline. However, the injection of these solvents and chemicals has a side effect on inhibition performance. Moreover, these chemicals require vast infrastructure such as storage tanks, injection pumps, a complex regeneration process, and subsea distribution pipelines. In addition, different ionsâ presence in the formation water may induce operational issues such as hydrate inhibitor loss and scale deposition. Gas hydrate and corrosion inhibitorâs mechanism, types, and applications in the petroleum industry have drawn much attention but ionic liquid-based multipurpose gas hydrate corrosion inhibitor (GHCI) behavior or performance is scarce in open scientific literature. This book chapter discusses the fundamentals of hydrate and corrosion formation, occurrence, and latest hydrate and corrosion chemical prevention methods along with updated literature review on the application of ionic liquid application in this field. The challenge of application of GHCl and understanding the chemistry of ionic liquids is presented. Prospects on multipurpose GHCIs for the oil and gas industry are also discussed briefly. Â© Springer Nature Switzerland AG 2020.